Understanding de novo onset of anxiety during COVID‐19: Pre‐pandemic socio‐emotional functioning in vulnerable children. Issue 2 (5th May 2022) - Adegboye, Dolapo; Lennon, Jessica; Batterbee, Olivia; Thapar, Anita; Collishaw, Stephan; Shelton, Katherine; Langley, Kate; Hobson, Christopher; Higgins, Andrea; van Goozen, Stephanie
Abstract: Background: There is a need to understand and mitigate the psychological impacts of the COVID‐19 pandemic for children known to be vulnerable. Data from prior to the pandemic are required to provide robust assessments of the socio‐emotional impacts of COVID‐19 and identify those who are more vulnerable. Method: This study capitalises on an ongoing UK study of primary school children (4–8 years) identified prior to the pandemic as "at risk" for mental health problems by teachers. We collected mental health and social‐emotional functioning data prior to the pandemic (Time 1) and re‐assessed this cohort ( N  = 143) via researcher‐led videocalls during lockdown (Time 2, summer 2020) and post‐lockdown, 12 months later (Time 3; summer 2021). Results: Mental health problems, particularly clinically significant anxiety, increased from 34% to 43% during lockdown and to 48% post‐lockdown. Parental mental health difficulties (anxiety and depression) were prevalent during lockdown (40%) but had decreased 1 year later (20%). Children who developed clinically significant anxiety during the pandemic had impaired socio‐emotional functioning at Time 1 (i.e., impaired emotion recognition, low self‐esteem and social problems) and a high proportion (44%) had no contact with any peers during lockdown, which may have contributed to their anxiety, especially their school anxiety. Conclusion: The pandemic appears to have exacerbated anxiety in already vulnerable children. A profile of socio‐emotional problems identified a group of children who developed significant anxieties during the pandemic. These socio‐emotional processes can be targeted for intervention to mitigate the negative mental health consequences of the pandemic and contribute to resilience in children.